Cooperative work and neuroeducation in mathematics education of future teachers: A good combination? - Procopio, Marcos; Fernandes Procopio, Leandra; Yáñez-Araque, Benito; Fernández-Cézar, Raquel (Frontiers in Psychology, 2022)
In order to respond to the new approaches in higher education, this paper presents the didactic experience of the implementation of a methodological approach based on cooperative learning and the literature review on neuroeducation in 53 students enrolled in the 3rd year of the degree in Early Childhood Education in the subject of Development of Logical-Mathematical Thinking and its Didactics II. The application of cooperative learning in combination with the literature review on neuroeducation aimed to teach future teachers how they should act with their future pupils (aged 3 to 6 years) with special educational support needs (SEN) at school. The design of the proposal to be used was also adjusted to the didactic resources available. The represented contents worked on were magnitudes, time, length, weight, and geometry. The data collected were the activities of the teacher training students (didactic proposals) adapted to the early childhood development stage. They were to be created, so that the main objective was that the undergraduate students would be able to solve the exercises as children would. The students were even challenged to make an exhibition in which they had to act as teachers and their classmates would be the children with SEN. The proposals were evaluated according to a rubric, with an emphasis on the students' teachers' awareness of students with SEN. To conclude, the degree of satisfaction of the student teachers with this methodology was high. This shows that learning neuroeducation and cooperative work makes future teachers know how to teach mathematics also to students with SEN.